Сomparative analysis of calculated and experimental studies of pallet movement speed on magnetic type brake roller - I. A. Sharifullin; A. L. Nosko; E. V. Safronov (Вестник СибАДИ, 2021)
Introduction. Increasing the efficiency of using a warehouse with a constant volume is an urgent task, the solution of which is possible through block or deep-lane storage systems. One such solution is the pallet flow rack, which saves up to 25% of the distance travelled by a forklift compared to the single-deep racks. The main element of the safe operation of the gravity roller conveyors used in a pallet flow rack is a brake roller. The most promising design is a magnetic (eddy current) type brake roller.The purpose of the work is to carry out a comparative analysis of the results of the calculated and experimental studies to determine the speed of movement of a pallet along a magnetic brake roller.Materials and methods. The research area is the magnetic brake roller. Its construction and description of work presented. The results of calculated and experimental study of the coefficient of magnetic viscosity presented.Results. The calculated and experimental dependences of the pallet movement speed along the magnetic brake roller were obtained. It was found that with an increase in the speed of movement of the pallet along the magnetic brake roller, the error of the mathematical model increases, and, first of all, after crossing with the straight line of a drag peak speed.Conclusions. A comparative analysis of the results of the calculated and experimental studies to determine the speed of movement of the pallet along the magnetic brake roller carried out. It was found that the developed design of a magnetic brake roller in the operating range of the pallet masses from 100 to 600 kg with up to 16 magnets located on one side of the disc, and from 100 to 1150 kg with up to 8 pairs of the magnets located on both sides of the disc, provides a speed control within the limits not exceeding the permissible speeds of the pallet movement on the gravitational roller conveyor. The verification of the mathematical model showed that the average value of the error of the mathematical model in the entire range of the pallet masses at speeds not exceeding the permissible speeds of pallet movement on a gravitational roller conveyor and below the drag peak speed is no more than 8.2%.